Reviewing Fundamental CO2 Adsorption Characteristics of Zeolite and Activated Carbon by In-situ Measurements With Radioactively Labelled CO2. Issue 3 (3rd July 2022) - Deng, Yimin; Seville, Jonathan Peter Kyle; Bell, Sarah Dawn; Ingram, Andrew; Zhang, Huili; Sweygers, Nick; Dewil, Raf; Baeyens, Jan; Appels, Lise
ABSTRACT: Gas adsorption is widely used in air pollution control, with mainly activated carbon and zeolites used as adsorbents. Although physical and chemisorption can be used, most air pollution applications involve physical adsorption, now also increasingly investigated for CO2 abatement from combustion gas. Empirical adsorption treatments have been presented since many decades, but solely rely on the comparison of adsorbate feed and exhaust concentrations of the adsorption bed. In-situ measurements, to study the absorbate/adsorbent interactions in real time, are compared in the present review when performed by a three-dimensional (3D) Positron Emission Tomography of an adsorbing 11 CO2 radioactive tracer on activated carbon versus a zeolite adsorbent. The overall results are validated by conventional exit gas analysis. Results are defining both the time-dependent adsorption parameters, such as the progressing adsorption front and Mass Transfer Zone along the adsorbent bed length, and enable to assess previous semi-empirical adsorption correlations toward their optimum validity in predicting adsorption isotherms, kinetics and mechanisms.